Cancer Burden in the Red Sea State, Sudan: A Ten Years of Incidence, Distribution, and Trends: (2016 - June 2025) - Widaa, Awad Abdalla (Journal of medical and pharmaceutical sciences, 2025)
Cancer is an increasing health concern in the Red Sea State while population-based data remain scarce. Aim: To describe adult cancer incidence, geographic distribution and trends in the Red Sea State between 2016 and 30 June 2025 and to assess the impact of the April 2023 armed conflict and patient displacement on registry measures. Patients and Methods: A descriptive retrospective review of all histopathologically confirmed adult cancer cases registered at Port Sudan Oncology Centre (POC) from 2016 to 30 June 2025 (n=3,265). Demographic and clinical data were abstracted from paper and electronic records; analyses used SPSS v20 to compute frequencies, age- and sex-specific and age-standardized rates; chi-square test evaluated associations (p<0.05). Results: A total of 3,265 cases were recorded (annual caseload ≈300–350; overall incidence 36.5/100,000). Females predominated (F:M = 1.74:1). Top five primary sites were breast (26.0%), leukaemia (12.4%), head & neck (7.7%), prostate (7.5%) and oesophagus (6.5%). The largest proportion was aged 59–78 (43.9%); 84.6% resided in Port Sudan. The 2023 conflict and subsequent displacement increased referrals to POC (≈21.4% of new patients in early 2024 were displaced). Conclusion: This is the largest contemporary survey of cancer burden in the Red Sea State. Findings highlight the urgent need to strengthen regional cancer registration, expand targeted prevention and screening, improve access to diagnostics and treatment, and plan resources to mitigate the impact of conflict on cancer care.